Cyberbullying Among Elementary School Students on TikTok Social Media Platform - Endang Sri Maruti; Inin Ananta (Madako Elementary School, 2024)
The trend of bullying in social media (ciberbullying) is a problem that is rife in the younger generation that occurs without knowing the victims such as school-age children which is then the important purpose of this research conducted. The analysis of bullying cases is examined by analyzing the blame for the misuse of  online social media platforms such as TikTok which is familiar to use among elementary school students which often causes physical and psychological clashes such as fights, ridicule, slander, threats, being a negative spectacle and being the object of gossip. This phenomenon causes anxiety in victims such as anger, shame, closing themselves and even antipathy to progress in learning. Qualitative methods with a content analysis approach  were emphasized in this study, but still require quantitative data information through the distribution of questionnaire instruments for 20 student respondents at SDN Pangongangan Madiun related to indications of cyberbullying behavior. The expected implications of this research are minimizing the negative impact  of ciberbullying and increasing students' social awareness to be wise in utilizing  the TikTok platform for more positive and educational activities.